Docência universitária: concepções de prática pedagógica do professor licenciado em Pedagogia - Carvalho, Viviane Alves (2016)
The topic area of this paper is the university professorship of professionals who are currently teaching and who have their first degree in Pedagogy. This reflection on professors’ professional development justifies itself bearing in mind an ever-changing reality, which significantly affects the goals and importance of education, hence the training of professors. This paper’s line of research is Knowledge and Educational Practices. Its objectives are to “investigate, study and understand which pedagogical input professors whose initial training was in pedagogy, have in their practice in the classroom. It also aimed at signaling the interactions that these professors establish with their peers and their teaching organization by means of the following study categories: conceptions of university professorship, professional training and professorship knowledge. The issue of studying university professorship, in general, has become a challenge in the academic milieu. Scientific research in this field of study has been intensified lately by researchers such as: Cunha (2005, 2002); Masetto (2012, 2003, 2001); Malusá (2012, 2005, 2001); Melo (2012, 2009); Pimenta and Anastasiou (2010); Tardif (2011, 2000); Zabalza (2004), among others. Nevertheless, there are difficulties as regards research references on professors who hold a degree in Pedagogy in Graduate Teaching. This paper is an exploratory-analytical research with both quantitative and qualitative approaches using mixed tools – closed affirmations ( Likert five-point Scale), and three open questions (Bardin Content Analysis). As target- group, we had the participation of 24 IES – Higher Degree Educational Institution pedagogues / professors. In summary, the findings have shown that in relation to professors’ teaching conceptions, there is no unity among the researched professors. They preferred not to speak out frequently choosing a more neutral position in their answers. Considering the area of professional development, these professors valued a specific, continual training and reflexive pedagogical practice. As far as professorship knowledge, the answers aligned in the direction of a more innovative paradigm; actually this is how they see their own pedagogical practice: innovative. They believe that the transformation of the world of knowledge and that of the world of work have a direct impact on their practices, yet they expressed a conservative behavior as regards planning their subjects.